Investigation of mental retardation in relation to bilingual and subcultural factors G. D. Mcgrath and Others. - Mcgrath, G. D. (Distributed by ERIC Clearinghouse, 1960)
The purpose of this study was to investigate the difference between true mental deficiency and pseudomental deficiency due to language, cultural, and socioeconomic limitations. The factors were studied by the method of repeated tests over a 3-year span in an adapted but relatively constant learning situation. Mental achievement, language tests, and sociological study of the children's environments were used as criteria. The subjects were 188 recent immigrant Mexican and Indian children in special classes for bilingual children. Mental retardation is apparent among some bilingual children but often is pseudo as the result of many factors, including socioeconomic attitudes, family background, and others. Typical school programs are not adequately designed to meet the needs or bring out the full potential of these bilingual children who have high mental abilities, as demonstrated by the fact that they have developed some facility with two languages. More studies are recommended and the necessity of continued work related to the field of bilingual children is made apparent throughout the study. (gc)